SIGNIFICANCE OF MALONDIALDEHYDE (MDA) IN DIABETIC COCHLEOPATHY - SUMATHI.K; JAMUNA RANI.A; SARAVANAN.D (International Journal of Pharma and Bio Sciences, 2013)
Cochleopathy is one of the morbid complication of diabetes mellitus (DM) leading to irreversible sensori-neural hearing loss. The aim of the study is to study the significance of MDA in diabetic cochleopathy. This is a cross sectional study which includes hundred diabetic patients attending tertiary health care center. Serum MDA levels were assayed by TBARS method (Thiobarbituric acid Reactive substances) , HbA1c by Ion-exchange chromatography & hearing by Pure-tone audiometry. Out of 100 diabetic patients, 87 had MDA level > 2 µmol/L, & out of 87 diabetic patients with MDA levels >2 µmol/L, 45 had hearing loss which is significant. From the results obtained, we find that the hearing impairment in diabetic patients is influenzed by the oxidative stress. So screening of the diabetic patients by estimating serum MDA levels & bone conduction by pure tone audiogram is advised so as to prevent the occurrence of diabetic cochleopathy & also the worsening of the disease complication.